Observations and simulation of intense convection embedded in a warm conveyor belt – how ambient vertical wind shear determines the dynamical impact - Oertel, Annika; Sprenger, Michael; Joos, Hanna; Boettcher, Maxi; Konow, Heike; Hagen, Martin; Wernli, Heini (Copernicus Publications, 2020)
Warm conveyor belts (WCBs) are dynamically important, strongly ascending and mostly stratiform cloud-forming airstreams in extratropical cyclones. Despite the predominantly stratiform character of the WCB's large-scale cloud band, convective clouds can be embedded in it. This embedded convection leads to a heterogeneously structured cloud band with locally enhanced hydrometeor content, intense surface precipitation and substantial amounts of graupel in the middle troposhere. Recent studies showed that embedded convection forms dynamically relevant quasi-horizontal potential vorticity (PV) dipoles in the upper troposphere. Thereby one pole can reach strongly negative PV values associated with inertial or symmetric instability near the upper-level PV waveguide, where it can interact with and modify the upper-level jet. This study analyses the characteristics of embedded convection in the WCB of cyclone Sanchez based on WCB online trajectories from a convection-permitting simulation and airborne radar observations during the North Atlantic Waveguide and Downstream Impact EXperiment (NAWDEX) field campaign (IOPs 10 and 11). In the first part, we present the radar reflectivity structure of the WCB and corroborate its heterogeneous cloud structure and the occurrence of embedded convection. Radar observations in three different sub-regions of the WCB cloud band reveal the differing intensity of its embedded convection, which is qualitatively confirmed by the ascent rates of the online WCB trajectories. The detailed ascent behaviour of the WCB trajectories reveals that very intense convection with ascent rates of 600 hPa in 30–60 min occurs, in addition to comparatively moderate convection with slower ascent velocities as reported in previous case studies. In the second part of this study, a systematic Lagrangian composite analysis based on online trajectories for two sub-categories of WCB-embedded convection – moderate and intense convection – is performed. Composites of the cloud and precipitation structure confirm the large influence of embedded convection: Intense convection produces locally very intense surface precipitation with peak values exceeding 6 mm in 15 minutes and large amounts of graupel of up to 2.8 g kg$^{−1}$ in the middle troposphere (compared to 3.9 mm and 1.0 g kg$^{−2}$ for the moderate convective WCB sub-category). In the upper troposphere, both convective WCB trajectory sub-categories form a small-scale and weak PV dipole, with one pole reaching weakly negative PV values. However, for this WCB case study – in contrast to previous case studies reporting convective PV dipoles in the WCB ascent region with the negative PV pole near the upper-level jet – the negative PV pole is located east of the convective ascent region, i.e., away from the upper-level jet. Moreover, the PV dipole formed by the intense convective WCB trajectories is weaker and has a smaller horizontal and vertical extent compared to a previous NAWDEX case study of WCB-embedded convection, despite faster ascent rates in this case. The absence of a strong upper-level jet and the weak vertical shear of the ambient wind in cyclone Sanchez are accountable for the weak diabatic PV modification in the upper troposphere. This implies that the strength of embedded convection alone is not a reliable measure for the effect of embedded convection on upper-level PV modification and its impact on the upper-level jet. Instead, the profile of vertical wind shear and the alignment of embedded convection with a strong upper-level jet play a key role for the formation of coherent negative PV features near the jet. Finally, these results highlight the large case-to-case variability of embedded convection not only in terms of frequency and intensity of embedded convection in WCBs but also in terms of its dynamical implications.